2022
DOI: 10.3390/biology11101394
|View full text |Cite
|
Sign up to set email alerts
|

Camouflage and Exploratory Avoidance of Newborn Cuttlefish under Warming and Acidification

Abstract: Ocean warming and acidification have been shown to elicit deleterious effects on cephalopod mollusks, especially during early ontogeny, albeit effects on behavior remain largely unexplored. This study aimed to evaluate, for the first time, the effect of end-of-the-century projected levels of ocean warming (W; + 3 °C) and acidification (A; 980 µatm pCO2) on Sepia officinalis hatchlings’ exploratory behavior and ability to camouflage in different substrate complexities (sand and black and white gravel). Cuttlefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Camouflage latency was considered as the time past acclimation until the photograph in which cuttlefish camouflaged in each substrate (strong mottle in sand and a dark uniform or disruptive pattern in gravel) was taken. The strength of disruptive patterns in gravel was evaluated through the difference between maximum and minimum pixel values (grayscale) in the frontal body plane (Court et al, (2022) adapted from Chiao et al, (2009)) read in the ImageJ 1.46r software (National Institute of Health, USA). Cuttlefish can be equally as well camouflaged when donning a dark uniform pattern instead of the classical disruptive.…”
Section: Camouflagementioning
confidence: 99%
See 1 more Smart Citation
“…Camouflage latency was considered as the time past acclimation until the photograph in which cuttlefish camouflaged in each substrate (strong mottle in sand and a dark uniform or disruptive pattern in gravel) was taken. The strength of disruptive patterns in gravel was evaluated through the difference between maximum and minimum pixel values (grayscale) in the frontal body plane (Court et al, (2022) adapted from Chiao et al, (2009)) read in the ImageJ 1.46r software (National Institute of Health, USA). Cuttlefish can be equally as well camouflaged when donning a dark uniform pattern instead of the classical disruptive.…”
Section: Camouflagementioning
confidence: 99%
“…However, the lower pixel intensity range observed was not due to cuttlefish resorting to dark uniform patterns, which is supported by the high minimum intensities observed (denoting an inability to produce dark tones). Interestingly, Court et al (2022) found that predicted ocean warming and acidification levels jointly elicit an intensification of the disruptive pattern in cuttlefish hatchlings. Consequently, can be surmised that deoxygenation and hypoxia do not trigger the allocation of energy to defensive behaviors during the cuttlefish's early ontogeny.…”
Section: Chronic and Acute Low Oxygen Yield Similar Outcomes On Cogni...mentioning
confidence: 99%
“…It is also possible to add a temporal dimension to the analyses. It may consist in assessing the latency of a chronic pattern ( Court et al, 2022 ) or its stability over short time periods ( Di Poï et al, 2014 ; Chabenat et al, 2021 ; Gouveneaux et al, in prep.). Otherwise, the comparison of camouflage quality at different ages during the first months is a simple way to assess whether the typically observed post-embryonic maturation of camouflage abilities is altered ( Dickel et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reproducibility of image analysis is also facilitated by the fact that cuttlefish usually stay still on the substrate and, therefore, exhibit a portion of its mantle relatively unchanged in size and extension (as opposed to octopodiforms which take on shapes and postures that usually conceal part of their skin). This feature could facilitate the adaptation of more complex quantification methods (e.g., the analysis of grey values profiles along some body axes; Court et al, 2022 adapted from Chiao and Hanion, 2001 ) to reveal more subtle color change alterations. Indeed, image analysis can be technically challenging and time-consuming, especially if the method is manual and several annotators have to analyze in parallel to avoid bias on the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation